Kepemimpinan Strategis dalam Masa Krisis Pandemi Covid-19 (Belajar dari Pemimpin Daerah Kota Tegal) - Joko Aji Wibowo; Maria Puspitasari (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The Covid-19 pandemic crisis is a test for Regional Leaders in showing their strategic leadership characteristics. One of the things that is interesting to study is the policy carried out by the Mayor of Tegal, which had caused controversy due to the announcement of the implementation of a local lockdown by closing the access to the inner city protocol roads and connecting roads between villages under his leadership. This research was made for the purpose of identifying and analyzing the strategic leadership of the Regional Leaders of the City of Tegal in overcoming the Covid-19 pandemic crisis and the impact of this leadership on Indonesia's national resilience. The method used is a qualitative approach with descriptive analysis techniques and secondary data collection through literature review. The results of the analysis of the Tegal Mayor's strategic leadership show efforts to facilitate the ability of the social system in Tegal City to adapt to the conditions of the Covid-19 pandemic and learn to overcome problems that arise. The strategic analysis is to implement strategic leadership through the objectives, methods and tools used to reduce the spread of Covid-19 in the Tegal City area. The role of human values and concern and cooperation of all parties is considered effective in dealing with crises. With these efforts, it can build stronger satisfaction and achievements in involving stakeholders who are more representative of the people's side.